(untitled) (Research, Society and Development, 2020)
This study deals with the analysis of rural companies showing the importance of environmental preservation in the face of economic development. The objective is to analyze this scenario of environmental relevance amid the negative impacts that may be caused with the use of innovative technologies and the irresponsible management of natural resources, looking for sustainable alternatives to change this scenario. As for the methodology employed, it uses the deductive approach method, the methods of interpretive and dialectical procedure, and the techniques of bibliographic and documentary research. The present research elucidates an alternative agriculture to replace the modern one that is, based on mechanisms that reduce the impacts to the environment and develop economically. In sequence, it shows the application of sustainable management in rural companies in order to become sustainable enterprises. Such application is analyzed based on the need for sustainable practices that promote economic development and preserve the environment. Therefore, it concludes that, based on the application of sustainability, rural companies that use sustainable mechanisms in their production process are able to meet the demands while conserving the environment and still develop economically, being able to be applied in companies rural areas.